Peningkatan Hasil Belajar Siswa dengan Menggunakan Model Pembelajaran Listening Team pada Mata Pelajaran IPS - Zubaidah Matondang (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2017)
This study aims to determine whether the use of learning model Listening Team can improve student learning outcomes. This research is a classroom action research conducted at SD Negeri 101768 Lesson Year 2015/2016. Subject of this research is student of class III which amounted to 24 people. Technique of collecting data is done by test method and observation method. Effectiveness research indicators in this assessment include student activities during learning activities and students' learning completeness in a classical way. The results showed the effectiveness of student learning reviewed through learning mastery that is equal to 83.3%. Increase in review through the learning activities of students is 92%. Based on the details of the results of the above research, then learning to use learning model Listening Teams in third grade students SD N 101768 TP 2015/2016 can improve student learning activities and improving student learning outcomes in terms of mastery of student learning classically on money history materials in Social Studies subjects.